Espaços comunitários para a infância e a juventude na contemporaneidade da "Terra Brasilis": o potencial na construção de cidade educadoras - Vasconcelos, Paulo Sergio Souza (2014)
This paper is an analysis of the dynamics that exist in the educational community spaces for children and youth in the contemporary "Terra Brasilis" as a potential for building educating cities. Issues related to the city, the community, childhood, youth, training and leisure spaces, education for human development, the territories of peaceful coexistence, the education intentionality of the metropolis, the right to use and occupy spaces of an educating municipality, creative potentials of the metropolis, the city as a theological space, the ethical values that must exist in an urban territoriality and the potential strength of sustainability in a city that educates have been addressed. This written project has its importance and its justification in the observance of the current matrix of society where humankind and the urban centers, which entered in a period of change, find themselves. The extent, understanding and above all velocity, probably never have had an equivalent in history. Overwhelmed with the human agglomerations the cities often lose their values and ethics in search of survival. This situation requires further study, reflection, analysis and construction of social and educational programs to respond effectively. Public and private powers, agents and local institutions could put together public policies to improve the quality of the civic life of their citizens, especially projects targeting the vulnerable populations - children and youth. These social strata would need to be empowered through education focused on human development that would lead to "another possible world" where local collectives and the public would give rise to growth opportunities, not only citizenship, but also as humanized territories, prepared to foster a more just and equitable society for all. The textual structure of this dissertation is made up of four chapters along with the conclusive considerations. In the first chapter we sought to elaborate conceptual mappings, in order to clarify the meanings of some terms that were used in the construction process of this dissertation. In the second chapter a critical and systematic study in the apparatus of educational spaces in a educating city, seeking to understand that urban spaces are educational territories for urban development, was made. In the third chapter, the city as a theological educating space, the central idea is to understand that a city that educates also makes us think about the physicality of its living places as theological spaces. In the fourth chapter, entitled the potential of building educating cities, this paper presents the assertion that community spaces provide their social interlocutors the potential energy to materialize the construction of educating cities, as well as the need for the existence of sustainability and ethical values in a city that educates. The last part concludes with the concern of presenting the texture of an urban pedagogy for an educating city, built on principles, values and virtues that make a human territoriality for both living spaces and as sites which potentiate educability.